The Marketing Strategic Planning of Alternative Energy Flows and Logistic Enterprise Activity - Kasian, Serhii; Bunyak, Vasyl; Moryak , Tetyana (Scientific Journal of Bielsko-Biala School of Finance and Law, 2021)
The systematic study of the current market for industrial products for the marketing chain “production – delivery to processing – processing – sale” Ukrainian scientists has been done. Formation of information, market relations in EU countries is characterized by considerable degree of transparency and competition during coordinating of resource logistic flows. it is advisable to research the direction of such functions to other mediated influence groups, such as: the public, power, stakeholders, who constantly interact in the marketing planning innovation space. Significant in the analysis of the needs of target customers is the innovative activity of the national airline Antonov Airlines, which is aimed at successfully coordinating the distribution of cargo movement in the context of globalization. Investigated activity, planning of private joint-stock company with foreign investments “The Dnipropetrovsk Oil Extraction Plant”. The enterprise is the participant of the international group of companies BUNGE & specializes on processing of seeds of sunflower and production of vegetable oil. In modern turbulent conditions, it is worth using methods for choosing the optimal structure of the logistics distribution channel of a high-tech product (alternative energy flows). The intensification of qualitative changes in the transformation of resource energy flows contributes to the diffusion of innovations